What we know about management accountants' changing identities and roles – a systematic literature review. Issue 3 (10th August 2020) - Wolf, Tanja; Kuttner, Michael; Feldbauer-Durstmüller, Birgit; Mitter, Christine
Abstract : Purpose: Academic interest in role changes of management accountants (MAs) has increased during the past two decades. Role changes imply identity reconstructions as they do not only require an external legitimacy, but professionals have to internalize a new role script. Thus, this paper aims to contribute to a comprehensive understanding of the ongoing changes concerning MAs by providing an identity perspective. Design/methodology/approach: This paper systematically reviews the literature on the changing role of MAs from an identity perspective, based on a conclusive sample of 64 articles. Findings: This review identified several external factors such as professional associations and educational institutions as well as organizational and individual factors that impact MAs' identity and act as change drivers. MAs' identity is linked with their image in the public and within the organization and is challenged by increasing demands, conflicting expectations and technological progress. Hence, the literature sample illustrates a fragmented and contradictory picture regarding the changes of MAs' identities and roles and displays that the idea of a simple movement from one identity to another is misleading. Furthermore, the identity perspective offers new issues for management accounting research, practice and education such as nested identity, multiple or desired identities. Originality/value: To the best of the authors' knowledge, this study is the first to review the literature of MAs' changing identities and roles from an identity perspective. This perspective enables a novel focus on internal views, perceptions and internalized meanings of MAs connected with their role instead of exclusively debating changed external behavior expectations.